Potential of three enhanced diatomaceous earths against Sitophilus zeamais Motschulsky and Prostephanus truncantus (Horn) on stored maize grain. (May 2020) - Zhanda, Justice; Mvumi, Brighton M.; Machekano, Honest
Abstract: Global health and environmental concerns against synthetic pesticides in stored-grain coupled with high cost, unavailability and inaccessibility of modern non-chemical grain treatment technologies in Africa are driving the need for low-cost and low-dose combination of readily available alternatives. Laboratory studies were conducted to determine the efficacy of non-registered low-dose food grade diatomaceous earths enhanced with natural grain protectants: IBS at 50, 75 and 100 ppm; IPE1 at 200, 300 and 400 ppm; IPE2 at 100, 150 and 200 ppm against Prostephanus truncatus and Sitophilus zeamais adult insects on maize. Adult insect mortality was assessed at 7, 14 and 21 days after treatment (DAT) while progeny emergence was assessed at 49 and 70 DAT for S. zeamais and P. truncatus, respectively. IBS caused significant (p < 0.05) P. truncatus and S. zeamais adult mortality at 14 and 21 DAT, respectively. Except for IPE1 at 400ppm, lower doses of IPE1 and IPE2 showed significantly low adult mortality (p < 0.05) (54-74%) on Sitophilus zeamais compared to IBS and the positive control. All rates of IPE1 and IPE2 were also not effective on P. truncatus adults, with significantly low mortality (p < 0.05) (18–38% compared to positive control). IBS at 75 and 100 ppm were effective on progeny suppression on both S. zeamais and P. truncatus but IPE1 at 400 ppm was effective on S. zeamais only. These results suggest the potential of IBS and IPE1 (at 400 ppm) as effective sustainable alternatives to synthetic grain protectants for small-scale farmers in sub-Saharan Africa who may not afford the modern non-chemical grain protection technologies. Field efficacy of these materials under typical farmer conditions is required.